Pengaruh Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Bismaniaga Lestari Medan - Inovia Akhsa Sijabat (Jurnal Niaga & Bisnis (e-journal), 2015)
This study aims to determine how the motivation to work at PT. Bismaniaga Lestari, how labor productivity at PT. Bismaniaga Lestari, how to influence work motivation on employee productivity at PT. Bismaniaga Lestari and type of motivation which greater influence on employee productivity at PT. Bismaniaga Lestari. Research is a form of associative research with quantitative approach. The population is the entire employee of PT. Bismaniaga Lestari that is 140 people and 58 people with formula samples Slovin. Data collection techniques with questionnaires/questionnaire, participant observation and document companies. Data analysis techniques used are validity, reliability test, normality test, simple linear regression data analysis, determination test and Pearson Product Moment Correlation.. The results based on the classification criteria of respondents to work motivation variables (variables X) that work motivation is at very high criteria. While the classification criteria of respondents to employee productivity variable (variable Y) are at moderate criteria. However, from the analysis of sub-variables as motivation, that internal motivation greater influence on employee productivity, while external motivation remains to be further enhanced by the management company. Based on a simple linear regression analysis of the data obtained regression equation Y=17.563+0.267X. Constants obtained from the equation of 17.563 and a regression coefficient of 0.267X variable. Test results of determination of R-Square of 0.333. That is, 33.3% of the variation employee productivity is determined by the role of work motivation. Positive values ​​on the interval r Pearson Product Moment coefficient is equal to 0.577 gives the relationship between the two variables is unidirectional and significant. Keywords: Work Motivation, Employee Productivity.